LA REDACCIÓN CIENTÍFICA: SCIENTIFIC WRITING - Almaguer Luaiza, Benito (Opuntia Brava, 2018)
El artículo trata acerca de los fundamentos teóricos conceptuales que sustentan la redacción de textos científicos, sus características, requisitos básicos de la redacción, la estructura dentro de la redacción científica y tipologías de los transtextos, además se ofrecen ejemplos que facilitan su aprehensión en profesores e investigadores. ABSTRACT This article deals with the theoretical support of writing scientific texts, its characteristics, basic requirements of writing, the structure within scientific writing and typology of transtexts. Besides, it offers samples that ease its learning in professors and researchers. KEY WORDS: Language, scientific text, scientific writing.